Universities as engines of inclusive innovation - Cole, Alex; Hayes, Sarah; Jopling, Michael; Jandrić , Petar (Proceedings of the International Conference on Networked Learning, 2026)
In a postdigital society, understood as characterised by rapid sociomaterial and technological change, AI solutionism amid complex geopolitics, pervasive uncertainty, and deepening inequalities, the civic role of universities is being re-examined. This chapter explores how universities can become engines of inclusive innovation by acting as architects, bridgers, and catalysts for ethical and responsible innovation and new avenues of collaborative networked learning. This requires disruption of many assumptions made within universities and in government policies regarding Knowledge Exchange (KE) policies and practices, civic agendas, and a reconsideration of the language that is routinely used to describe potential business, research and cross-sector partners in the community. Drawing on the complementary research and practice of the four co-authors, the paper integrates theoretical and practical insights from recent academic publications and community focused projects. We demonstrate how seed-funded co-designed listening events, catalyst conversations, and community innovation hubs create enabling infrastructures to confront digital and data disadvantage, amplify youth and community voices, and foster trust-based, equitable partnerships. Through a synthesis of theory and practice, we argue that universities, when acting ethically and relationally, can reimagine innovation and KE as a civic good in partnership with diverse community stakeholders. In so doing, there is an opportunity to critically reposition narrow understandings of KE, as instigated and enacted by universities, and reimagine these as co-created civic forms of networked learning. This reframing positions the university, not as an extractive ivory tower, but as a receptive, living ecosystem of inclusive innovation capable of co-shaping equitable futures in uncertain postdigital times.